Struktur dan Fungsi Sosial Cerita Rakyat Legenda Batu Busuak di Koto Tuo Limau Manis Kecamatan Pauh Kota Padang - Nabila Nabila; Zulfadhli Zulfadhli (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This article describes the structure of the folklore of the Batu Busuak legend in Koto Tuo Limau Manis, Pauh District, Padang City; and the social function of the folklore of the Batu Busuak legend in Koto Tuo Limau Manis, Pauh District, Padang City. This study used a qualitative approach using descriptive data originating from the folklore of the Batu Busuak legend in Koto Tuo Limau Manis, Pauh District, Padang City, which was collected through two stages. In the first stage of recording the legend of Batu Busuak folklore. In the second stage after recording folklore, after that collect data on the storytelling environment using recording, observation and interview techniques. Data analysis was carried out in four stages: (1) matching data with transcription and transliteration of data (2) analyzing data (3) discussing the results of data analysis (4) reporting the results of the analysis. This study found that the first structure of the folklore legend of Batu Busuak in Koto Tuo Limau Manis, Pauh District, Padang City consists of (a) style of language, (b) characters and characterizations, (c) setting (d) plot, (e) theme (f ) mandate. The second is the social function of the folklore of the Batu Busuak legend in Koto Tuo Limau Manis, Pauh District, Padang City, among others, to (a) educate, (b) pass on, (c) as identity.